Inibição do vírus da hepatite C utilizando siRNAs direcionados para o genoma viral e proteínas celulares Hsps - Braga, Ana Cláudia Silva [UNESP] (2013)
Hepatitis C is a consequence of infection by hepatitis C virus (HCV) and it is estimated that approximately 150 million people are chronically infected worldwide. Several studies have demonstrated interactions between viral and host proteins during the HCV replication cycle and these interactions might be used for development of new therapies against hepatitis C. The heat shock proteins (Hsp) are cellular proteins that interact with proteins of HCV and inhibition of these proteins could reduce viral replication. In this study, cellular proteins Hsp90 and Hsp27 were inhibited by siRNA targeting the mRNA of these proteins in combination with siRNA to viral 5'UTR region, NS3 and NS5A. We used a stable cell line expressing HCV subgenomic replicon and all siRNA molecules targeting the viral genome showed effectiveness in reducing viral replication. The best response was achieved by siRNA 5'UTR, which showed good results on long term studies. The inhibition of cellular protein Hsp27 increased virus replication, but knockdown of Hsp90 showed reduced viral replication. Use of this molecule together with the siRNA molecule directed to 5'UTR showed a decrease of more than 90% viral replication. However, the prolonged inhibition of Hsp90 led to cell death, demonstrating the important role of this protein in cell survival. Finally this work suggests that the combination therapy of siRNAs can be an effective alternative to treat hepatitis C in patients with HCC since reduction of Hsp90 expression if effective on tumor suppression and in HCV replication